Investment in Commodity Stocks as Way to Minimize Risks in Crisis - D. A. Arkadev; Yu. V. Lyandau (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Managing stocks in crisis is an effective method of providing sustainable functioning of the company and maintaining sales on the necessary level. To arrange this process it is essential to identify groups of products bringing high profit, products being in demand and products, which should be denied, as their sales are no higher than 2% of the total sales. The authors consider management of finished commodity stocks as a method to provide sustainability in crisis, in particular, pandemic. At the same time they highlight the key factors of stock monitoring, including possibility to build-up moderate stocks of free cash, methods of building-up and gaining commodity stocks, keep the balance between stock costs and costs of their maintenance, etc. To raise the efficiency of stock management the authors propose the following solutions for accumulating cash: crediting as the easiest way of raising funds to get stocks, which can affect negatively the finance sustainability of the organization; emergency meeting of proprietors and informing them about the strategy of crisis counteracting, including delay of paying dividends; building-up the urgent reserve and discharging unnecessary employees or transferring them on parttime work; discounts and sales, which can clear stock-houses and get needed funds. The article gives classification of products proceeding from 5 groups: leading products, accompanying products, substitutes, complex products and status products, each of the groups was characterized.